2011
DOI: 10.1007/s10646-011-0826-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial extracts containing microcystins affect the growth, nodulation process and nitrogen uptake of faba bean (Vicia faba L., Fabaceae)

Abstract: The use of irrigation water containing cyanobacterial toxins may generate a negative impact in both yield and quality of agricultural crops causing significant economic losses. We evaluated the effects of microcystins (MC) on the growth, nodulation process and nitrogen uptake of a Faba bean cultivar (Vicia faba L., Fabaceae), particularly the effect of MC on rhizobia-V. faba symbiosis. Three rhizobial strains (RhOF4, RhOF6 and RhOF21), isolated from nodules of local V. faba were tested. The exposure of rhizobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…PS II fluorescence was less sensitive than plant biomass, varying only in plants exposed to the highest toxin dose . Lahrouni et al (2012) reported differences in growth of rhizobia inoculated Medicago sativa (e.g. shoot and root DW variations) when exposed for 6 weeks to 100 lg/L MC M. aeruginosa extracts.…”
Section: Physiological Effects Of Toxic M Aeruginosa Extract In Ricementioning
confidence: 99%
See 1 more Smart Citation
“…PS II fluorescence was less sensitive than plant biomass, varying only in plants exposed to the highest toxin dose . Lahrouni et al (2012) reported differences in growth of rhizobia inoculated Medicago sativa (e.g. shoot and root DW variations) when exposed for 6 weeks to 100 lg/L MC M. aeruginosa extracts.…”
Section: Physiological Effects Of Toxic M Aeruginosa Extract In Ricementioning
confidence: 99%
“…MCs have been associated with the inhibition of germination and growth of several agricultural and forage plants (Crush et al 2008;El Khalloufi et al 2011;Saqrane et al 2008). MCs were shown to inhibit the nodulation of fava bean (Vicia faba) and alfalfa (Medicago sativa) (El Khalloufi et al 2011;Lahrouni et al 2012). This condition may have implications in nitrogen uptake and development of leguminous plants.…”
Section: Introductionmentioning
confidence: 99%
“…Growth inhibition has also been reported in other crops [19,20]. MCs also have a negative impact on seed germination and root development [20,21,22,23] and have recently been shown to inhibit nodulation and Rhizobia growth with the potential for impairment of nitrogen uptake in leguminous crops [24,25]. Moreover evidence was collected at the molecular level, which highlighted the physiological stress of the plants after exposure to MCs [20,24,26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Inoculums preparation: We used the same protocol reported above in the paragraph "Phosphate solubilization test on agar medium". The inoculum was prepared by growing the rhizobial strain in YEM liquid medium at 28°C for 2-3 days to obtain an optical density (OD) of 1 at 600 nm (approximately 10 9 colonies forming units (CFU)/mL) as described previously (Lahrouni et al, 2012;Oufdou et al, 2014). Inoculation and transfer to pot: Uniformly-germinated seedlings were immersed for 30 min in individual rhizobial liquid culture of each of the tested strains RHOF147, RHOF174, RHOF170 or RHOF171.…”
Section: Methodsmentioning
confidence: 99%